Effect of Bleaching and Thermocycling on Resin-Enamel Bond Strength - Horieh Moosavi; Hamideh Sadat Mohammadipour; Marjaneh Ghavamnasiri; Sanaz Alizadeh (International Journal of Biomaterials)
The aim of this study was to evaluate the effect of bleaching and thermocycling on microshear bond strength of bonded resin composites to enamel. Enamel slices were prepared from ninety-six intact human premolars and resin composite cylinders were bonded by using Adper Single Bond 2 + Filtek Z350 or Filtek silorane adhesive and resin composite. Each essential group was randomly subdivided to two subgroups: control and bleaching. In bleaching group, 35% hydrogen peroxide was applied on samples. Thermocycling procedure was conducted between 5°C and 55°C, for 3.000 cycles on the half of each subgroup specimen. Then microshear bond strength was tested. Methacrylate-based resin composite had higher bond strength than silorane-based one. The meyhacrylate-based group without bleaching along with thermocycling showed the most bond strength, while bleaching with 35% carbamide peroxide on silorane-based group without thermocycling showed the least microshear bond strength. Bleaching caused a significant degradation on shear bond strength of silorane-based resin composites that bonded using self-etch adhesive resin systems.